THE TRANSCARPATIAN BOARDING SCHOOLS ACTIVITY IN THE FIRST HALF OF THE XX CENTURY - Cherepania, Mariia (Mountain School of Ukrainian Carpaty, 2021)
The basic educational institutions establishment and operation causes the problem of providing students with living conditions in the case of opportunities absence for their daily transportation to the basic educational institution. That actualizes the problem of creating school dormitories or boarding schools nowadays. Boarding schools also operated in Transcarpathia in the first half of the twentieth century. Purpose of the study is to provide a retrospective analysis of the boarding schools activity in Transcarpathia in the first half of the twentieth century. The methods: search and bibliographic in order to study archival, library catalogs, collections, descriptions and bibliographic publications; archival sources content analysis and materials on the boarding schools activity. Results. The article reviews the boarding schools activity in Transcarpathia in the first half of the twentieth century, the emergence of which was due to the adoption in 1868 of the Law "On Education", according to which the Transcarpathian lands, part of the Austro-Hungarian Empire, began educational institutions’ rapid development from public primary schools to civic ones, as well as gymnasiums, lyceums, teachers' seminaries. Mostly these institutions were located in the modern Transcarpathia lowlands in the cities of Uzhgorod, Mukachevo, Beregovo, Nad Sevlyush, so students from remote and mountainous areas needed living conditions at the place of study. Boarding schools were organized at public expense and with the support of privat individuals and charities. The boarding schools provided round-the-clock students’ staying and organized life activities in their free time. To ensure the boarding schools activity, a manager, prefects (pedagogical mentors, educators), a spiritual manager, as well as support staff were appointed.